Beneficial Effects of Schisandrin B on the Cardiac Function in Mice Model of Myocardial Infarction - Chen, Pengsheng; Pang, Sisi; Yang, Naiquan; Meng, Haoyu; Liu, Jia; Zhou, Ningtian; Zhang, Min; Xu, Zhihui; Gao, Wei; Chen, Bo; Tao, Zhengxian; Wang, Liansheng; et al. (PLOS ONE, 2013)
The fruit of Schisandra chinensis has been used in the traditional Chinese medicine for thousands of years. Accumulating evidence suggests that Schisandrin B (Sch B) has cardioprotection effect on myocardial ischemia in vitro. However, it is unclear whether Sch B has beneficial effects on continuous myocardial ischemia in vivo. The aim of the present study was to investigate whether Sch B could improve cardiac function and attenuate myocardial remodeling after myocardial infarction (MI) in mice. Mice model of MI was established by permanent ligation of the left anterior descending (LAD) coronary artery. Then the MI mice were randomly treated with Sch B or vehicle alone. After treatment for 3 weeks, Sch B could increase survival rate, improve heart function and decrease infarct size compared with vehicle. Moreover, Sch B could down-regulate some inflammatory cytokines, activate eNOS pathway, inhibit cell apoptosis, and enhance cell proliferation. Further in vitro study on H9c2 cells showed similar effects of Sch B on prevention of hypoxia-induced inflammation and cell apoptosis. Taken together, our results demonstrate that Sch B can reduce inflammation, inhibit apoptosis, and improve cardiac function after ischemic injury. It represents a potential novel therapeutic approach for treatment of ischemic heart disease.